PERPUTARAN MODAL KERJA, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN DAN LIKUIDITAS PENGARUHNYA TERHADAP PROFITABILITAS (Studi kasus pada Bursa Efek Indonesia periode 2016-2018) - Trias Umi Ulfa; Listyorini Wahyu Widati (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
This research analyzes the effect of Working Capital Turnover, Growth, Size and Liquidity on Profitability (Study at Manufacture Companies listed on the Indonesia Stock Exchange for the 2016-2018 period). There are population of 143 Manufacture Companies listed on the Indonesia Stock Exchange. The sample selection method uses purposive sampling which is based on predetermined criteria, then obtained total sample are 44 manufacture companies during 2016-2018 period. The analytical tool use is multiple linear regression . The results this research show that working capital turnover and growth have not effect on profitability, while size and liquidity have effect on profitability. Keywords : Working Capital Turnover, Growth, Size, Liquidity, Profitability